Effect of perioperative ONS combined with intestinal microecology in patients with colorectal cancer: a randomized clinical trial - Liu, Xuanjun; Mao, Weixu; Zhao, Guowei; Liao, Juan; Li, Qigang; He, Gan (Frontiers in Nutrition, 2025)
PurposeTo investigate the combined effects of oral nutritional supplement (ONS) and intestinal microecology on postoperative nutrition status, inflammatory response and intestinal flora regulation colorectal cancer (CRC) patients.MethodsThis prospective single-center randomized controlled trial (RCT) was conducted at Chongqing Yongchuan Hospital between December 2023 and December 2024. CRC patients were randomly assigned to one of two groups: a control group receiving ONS (55.8 g per dose, three times daily) or a test group receiving ONS (55.8 g per dose, three times daily) combined with bifidobacteria (1.5 g per dose, three times daily).ResultsA total of 62 patients who undergoing radical colorectal cancer resection were enrolled. Participants were equally randomized into control and test groups (n = 31 each). At baseline, no significant differences in demographic characteristics, nutritional status, or inflammatory markers were observed between groups (p > 0.05). Prealbumin (PA; 174.0 ± 38.0 g/L vs. 149.7 ± 42.9 g/L, t = −2.358, p = 0.022), albumin (ALB; 36.6 ± 3.3 g/L vs. 33.1 ± 4.0 g/L, t = −3.745, p < 0.000), total protein (TP; 65.8 ± 5.1 g/L vs. 62.5 ± 6.3 g/L, t = −2.266, p = 0.027), and the changes in ΔT3–T2 in PA (32.9 ± 36.1 g/L vs. 13.3 ± 34.9 g/L, t = −2.180, p = 0.033), ALB (4.0 ± 4.5 g/L vs. 1.0 ± 3.7 g/L, t = −2.862, p = 0.006), and TP (7.5 ± 5.9 g/L vs. 4.0 ± 5.9 g/L, t = −2.333, p = 0.023) were significantly greater in the test group than in the control group. The reduction in C-reactive protein (CRP) from T2 to T3 (42.1 (27.1, 62.9) mg/L vs. 26.8 (10.7, 46.4) mg/L, Z = −2.752, p = 0.006) was significantly greater in the test group. Fecal DNA fingerprint analysis revealed that, compared with the control group, the test group presented significantly greater intestinal flora species richness and abundance. The time to first defecation was significantly shorter in the test group (4.5 ± 1.8 vs. 5.9 ± 1.7 days, t = 3.132, p = 0.003).ConclusionPerioperative ONS combined with intestinal microbiota interventions improves postoperative nutritional status, modulates inflammatory dynamics, and accelerates intestinal function recovery. However, these interventions show limited impact on hospitalization duration and complication rates.